If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 2c + -9 Reorder the terms: 25 = -9 + 2c Solving 25 = -9 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 25 + -2c = -9 + 2c + -2c Combine like terms: 2c + -2c = 0 25 + -2c = -9 + 0 25 + -2c = -9 Add '-25' to each side of the equation. 25 + -25 + -2c = -9 + -25 Combine like terms: 25 + -25 = 0 0 + -2c = -9 + -25 -2c = -9 + -25 Combine like terms: -9 + -25 = -34 -2c = -34 Divide each side by '-2'. c = 17 Simplifying c = 17
| 9x-4(3x-2)=4 | | 5x=2(x+30) | | 3b+15=27 | | m+2=15 | | 9x-19=7x+11 | | 15x^3+25x^2-60x= | | 8t-11=5t+19 | | -2(18-3t)=7y+2y | | -(5y+2)-(-4y-8)=1 | | 4-x=-5 | | 2(x+30)= | | 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 | | 54=(17x+3)+(25x+9) | | 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 | | 4(x+1)=8 |